Pengaruh Keberagaman Tenaga Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan di Kota Tangerang Selatan - Yulianto, Eko; Wicaksono, Bimo; Prasetio, Teguh (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to investigate the influence of workforce diversity and work environment on employee performance in South Tangerang City, Banten. Employing a quantitative approach, the research involved 150 respondents selected through Convenience sampling. The results of the t-test analysis indicate that workforce diversity and the work environment significantly affect employee performance (sig < 0.05). The coefficient of determination (R2) at 0.388 indicates that workforce diversity and the work environment contribute 38.8% to employee performance. While providing valuable insights, this study has limitations such as sampling methods and geographical coverage. Future research could deepen the understanding by incorporating qualitative aspects and considering additional factors influencing employee performance.